When Financial Stress and Monetary Policy Interplay with Economic Dynamics in the Eurozone: Multiple Shocks Effects - Zihala, Patrik; Sinicakova, Marianna; Sulikova, Veronika (Transformations In Business & Economics, 2025)
The aim of this paper is to examine the relationship between financial stress, as measured by the Composite Indicator of Systemic Stress (CISS), and macroeconomic variables, including GDP, inflation, unemployment and the ECB’s monetary tools. Using a vector autoregression (VAR) model, we analyse euro area data over the period 1999 to 2023 to assess the dynamic influences and their relative strength. The study estimates impulse response functions (IRFs) and forecast error variance decomposition (FEVD) to interpret the effects of multiple shocks, including multiple shocks from 2020 onwards caused by the COVID-19 pandemic, the war in Ukraine, and the energy crisis. Our findings suggest that increased financial stress undermines the effectiveness of traditional ECB instruments such as the main refinancing operations, negatively impacts GDP and increases unemployment. The FEVD results indicate that financial stress accounts for a significant part of the variability in unemployment, suggesting that financial stress indirectly affects labour demand and investment. In addition, GDP shocks explain a large share of unemployment variability across the ten observation periods. The results underline the need for flexible monetary responses in times of crisis and provide deeper insights into how monetary policy, financial shocks, and economic determinants interact to optimise policy decisions. The paper fills a gap in empirical research by analysing financial stress over a longer period, during which several crises and multiple shocks have occurred since 2020, highlighting the importance of observing the interactions of selected variables in each period of the business cycle, especially in the period of multiple shocks.
Keywords: financial stress; monetary policy; vector autoregression model; impulse-response functions; eurozone